Surakiart Sathirathai [Thailand, Deputy Prime Minister] - Sathirathai, Surakiart (Institutional Knowledge at Singapore Management University, 2015)
A former Deputy Prime Minister of Thailand, Surakiart Sathirathai is a long-time academic and who has also sat on many boards of companies. He shares with DNA his thoughts on the qualities that make a good leader, as well as what is lacking in leaders today – the ability to communicate to their followers.